Agency costs and corporate performance: Analysis of public listed companies in Bursa Malaysia - Nur Syuhada Wahida, Osman (2014)
The agency theory is one of the company’s theories in a way that company is explained as a set of contractual explicit of implicit relationships between principal (shareholders) and agent (management). The role of second party is to perform certain tasks and authorized to make decisions on behalf of the first party. Meanwhile corporate performance is very crucial for market efficiency since it will influenced the decision made by the market players and internal investors of the Companies. This study examines the relationship of agency costs with corporate performance. Five variables of agency costs proxies are analysed: Debt Ratio, Firm’s size, Growth, Expense and Efficiency. While the corporate performance is measured by Return on Assets (ROA) and Return on Equity (ROE) . ROA gives an idea as to how efficient management is at using its assets to generate earnings while ROE measures a corporation’s profitability by revealing how much profit a company generates with the money shareholders have invested. Besides, this study examined whether there are any correlation between agency costs which is proxied by Debt Ratio, Firm’s size, Growth, Expense and Efficiency Ratio; against Corporate Performance for the Top 50 and Bottom 50 Public Listed Companies in Bursa Malaysia. This study used secondary data which is the data from Public Listed Companies in Bursa Malaysia. From the total 814 population, the 100 sample was taken from different categories which is the Top 50 and the Bottom 50 companies covering over period of 5 years from 2008 to 2012. It is found that for a certain extent, the Agency costs play an important roles in relation to the Corporate Performance.The result gathered after analyzing the data acquired from Bursa Malaysia explained that only Firm’s size, Expense and Efficiency Ratio has the relationship with the significant value of 0.000. Debt ratio and growth variables was not significant with Corporate Performance